2015
DOI: 10.1186/s13059-014-0576-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid reprogramming of epigenetic and transcriptional profiles in mammalian culture systems

Abstract: BackgroundThe DNA methylation profiles of mammalian cell lines differ from those of the primary tissues from which they were derived, exhibiting increasing divergence from the in vivo methylation profile with extended time in culture. Few studies have directly examined the initial epigenetic and transcriptional consequences of adaptation of primary mammalian cells to culture, and the potential mechanisms through which this epigenetic dysregulation occurs is unknown.ResultsWe demonstrate that adaptation of mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 63 publications
7
114
1
Order By: Relevance
“…Similarly, the Ewing sarcoma PDX models evaluated in this study were negative for PDGFC expression, despite previous work identifying PDGFC as a target gene of the EWS-FLI1 fusion transcription factor (42). These data are suggestive of potential alterations in the tumor transcriptome when cultured or propagated outside of its native environment and are reminiscent of a previous report describing changes in the epigenome and transcriptome of mammalian cells isolated from primary tissues upon exposure to cell culture (43). Furthermore, a recent study demonstrated that an anti-PDGFRa polyclonal antibody frequently used in previous IHC analyses cross-reacts with PDGFRb, further confounding previous reports regarding the prevalence of PDGFRa expression in pediatric bone and soft tissue tumor patient samples (44).…”
Section: Discussionmentioning
confidence: 35%
“…Similarly, the Ewing sarcoma PDX models evaluated in this study were negative for PDGFC expression, despite previous work identifying PDGFC as a target gene of the EWS-FLI1 fusion transcription factor (42). These data are suggestive of potential alterations in the tumor transcriptome when cultured or propagated outside of its native environment and are reminiscent of a previous report describing changes in the epigenome and transcriptome of mammalian cells isolated from primary tissues upon exposure to cell culture (43). Furthermore, a recent study demonstrated that an anti-PDGFRa polyclonal antibody frequently used in previous IHC analyses cross-reacts with PDGFRb, further confounding previous reports regarding the prevalence of PDGFRa expression in pediatric bone and soft tissue tumor patient samples (44).…”
Section: Discussionmentioning
confidence: 35%
“…40 In addition to its role in DNA demethylation, 5hmC is a stable and functional epigenetic mark 41 and is enriched in the bodies of actively transcribed genes, at a number of transcription start sites, and at CTCF binding sites. 30,42,43 We identified significant enrichment of 5hmC at DMR2 and, although 5hmC is also known to be present at some imprinted DMRs, including across IGF2-H19, its precise role at these loci is unclear. 30 However, studies that show that H19 remains highly enriched for 5hmC in cell culture despite the global loss of 5hmC elsewhere, 43 and that such loci are also protected from demethylation in the post-fertilization embryo, 44 suggest that 5hmC dynamics at imprinted loci may differ from those in the remainder of the genome.…”
Section: Discussionmentioning
confidence: 97%
“…30,42,43 We identified significant enrichment of 5hmC at DMR2 and, although 5hmC is also known to be present at some imprinted DMRs, including across IGF2-H19, its precise role at these loci is unclear. 30 However, studies that show that H19 remains highly enriched for 5hmC in cell culture despite the global loss of 5hmC elsewhere, 43 and that such loci are also protected from demethylation in the post-fertilization embryo, 44 suggest that 5hmC dynamics at imprinted loci may differ from those in the remainder of the genome. Additionally, since 5hmC may be an intermediate in the DNA demethylation pathway, 5hmC at DMRs could result from the conversion of 5mC during the demethylation process.…”
Section: Discussionmentioning
confidence: 97%
“…Third, the genome-wide epigenetic changes that occur with adaptation to cell culture (e.g., see ref. 35) might preclude the generation of H3K27me3 marks in cultured DSCs.…”
Section: Methodsmentioning
confidence: 99%